Pathological changes of immunized mice with Trichophyton mentagrophyte lyophilized antigen: Radam, S. A. and Faleh, E. B. - A., Radam S. (The Iraqi Journal of Veterinary Medicine, 2013)
The study was carried to investigate the pathological effect of lyophilized antigen of Trichophyton mentagrophytes in mice. Fifty mice were divided into three groups. The first group 20 mice were immunized subcutaneous (s/c) with 0.5 ml of T.mentagrophyte antigen 20 µgm/ml, by two doses, 14 day intervals, between them. The second group 20 mice and third group 10 mice considered as positive and negative control groups respectively. After 30 days post immunization first and second groups were challenged intradermal I/d. with 0.1 ml of fungal suspension contain (1×107 ml) of viable virulence T.mentagrophyte while the third group injected intraperitoneally I/P. with 0.5 ml of sterile phosphate buffer saline. All mice of the first and second groups were sacrificed at (5, 14, 30 and 60) days post challenge for gross and histopathological examination. Histopathologically the second group showed epidermal hyperkeratosis with appearance of crust lesions seen with abscess formation especially in early stage of lesion, while the main feature of advance cases were characterized by folliculitis with fungal hyphae invasion in all epidermal and dermal layers together with eosinophilic infiltration. Mild pathological changes were seen in the 1st immunized group characterized by infiltration of mononuclear cells mainly macrophages in dermal connective tissue with dense proliferation of collagenous fibers , appearance of young fibroblasts together with cellular hypodermal infiltration of eosinophil no evidence of clear follicular lesions were seen. Lyophilized antigen of T.mentagrophyte can be considered as an effective immunogen for protecting mice against T.mentagrophyte infection and it is synchronized with its dose.